An In-Depth Theoretical Exploration of Data Mining in the Healthcare Sector: Techniques, Challenges, and Future Directions (International Journal of Food and Nutritional Sciences, 2023)
Data mining is a complex process aimed at uncovering hidden patterns within vast datasets. As a rapidly expanding discipline, it integrates statistics, visualization techniques, machine learning, and other data handling and knowledge discovery methods to reveal underlying trends and relationships within data. With the proliferation of the internet and mobile technology, data volumes are growing at an unprecedented rate, making analytics a critical focus across industries, both in IT and beyond. In particular, the healthcare sector is seeing increased exploration of data mining and machine learning applications to address data-intensive challenges. The demand for data warehouses is rising in healthcare, driven by the growing incidence of diseases, which is closely related to population growth and evolving lifestyles.